Astragalus Polysaccharide Inhibits Autophagy and Apoptosis from Peroxide-Induced Injury in C2C12 Myoblasts - Yin, Yi; Lu, Lu; Wang, Dongtao; Shi, Ying; Wang, Ming; Huang, Yanfeng; Chen, Dexiu; Deng, Cong; Chen, Jiebin; Lv, Peijia; Wang, Yanjing; Li, Chengjie; et al. (Cell biochemistry and biophysics, 2015)
The aim is to study the effects and underlying mechanisms of astragalus polysaccharide (APS) on the peroxide-induced injury in C2C12 myoblasts in vitro. Cell viability in the presence or absence of APS was detected by the methyl thiazolyl tetrazolium colorimetric assay. The autophagosomes were observed by electron microscopy to examine the influence of APS on autophagy caused by H 2 O 2 in C2C12 cells, and the percentage of apoptosis cells was measured by flow cytometry. To further confirm the effect of H 2 O 2 on C2C12 cells, the protein expression of LC3 and RARP, which are the markers of autophagy and apoptosis, respectively, was analyzed by Western blot, as well as the expression levels of p-p70S6K, p70S6K, Bcl-2, Bax, cyto-C, and Caspase-3, to reveal the underlying mechanisms. We observed multiple effects of APS on C2C12 functionality. APS treatment of C2C12 cells at 1 mg/mL reduced cell viability to less than 70 %, and analysis by electron microscopy revealed that APS also reduced the number of H 2 O 2 -induced autophagosome formation. Similarly, APS abated the H 2 O 2 -mediated increase in cell apoptosis, which was accompanied by the inhibition of LC3 II and RARP that are normally upregulated by H 2 O 2 . The expression of p-p70S6K and p70S6K, however, remained unchanged in C2C12 cells in the Control, H 2 O 2 and H 2 O 2 + APS groups. In addition, APS promoted the expression of protein Bcl-2 in H 2 O 2 -treated C2C12 cells, but did not change Bax, thus reducing the Bax/Bcl-2 ratio that in turn prevented the release of cytochrome c and the activation of caspase-3. APS inhibits the autophagy and apoptosis induced by peroxide injury in C2C12 myoblasts through two independent signaling pathways: the mTOR-independent pathway for the inhibition of autophagy, and the caspase-3-dependent pathway for the suppression of apoptosis.